On Trade Policy Preference and Offshoring Ties - Subhayu Bandyopadhyay; Arnab K. Basu; Nancy H. Chau; Devashish Mitra (Institute of Labor Economics (IZA), 2022)
This paper unpacks the role of the domestic content of imports as a novel source of policy interdependence along the global supply chain. We show how a rise in local contents embodied in imports can skew national trade policy preferences, and pull upstream and downstream countries in asymmetric ways with respect to (i) the nature of unilaterally optimal trade policy prescriptions, and (ii) the attractiveness of leveraging market access-based dispute settlement procedures. We discuss the pros and cons of deep trade integration as a remedy, involving well-enforced labor standards both upstream and downstream as an integral part of trade agreements.
Keywords: F11; F13; F16; F66; O19; O24; 330; offshoring; dispute settlement reciprocity; labor standards